2017
DOI: 10.1007/s11356-017-8924-6
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of marine fauna by chlordecone in Guadeloupe: evidence of a seaward decreasing gradient

Abstract: Chlordecone is an organochlorine pesticide, used in the Lesser Antilles from 1972 to 1993 to fight against a banana weevil. That molecule is very persistent in the natural environment and ends up in the sea with runoff waters. The objective of the present study is to evaluate the level of contamination in several trophic groups of marine animals according to their distance from the source of pollution. Samples of suspended matter, macroalgae, herbivorous fishes, detrivorous crustaceans, zooplanktivorous fishes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…This decreasing gradient of chlordecone from the coast to the open sea was previously identified [ 18 ] when studying spatial variations of the level of chlordecone contamination in different trophic groups. These results indicated that marine organisms are contaminated by chlordecone by direct contact with seawater and highlighted the existence of a bioconcentration phenomenon in these areas.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…This decreasing gradient of chlordecone from the coast to the open sea was previously identified [ 18 ] when studying spatial variations of the level of chlordecone contamination in different trophic groups. These results indicated that marine organisms are contaminated by chlordecone by direct contact with seawater and highlighted the existence of a bioconcentration phenomenon in these areas.…”
Section: Discussionsupporting
confidence: 53%
“…Since 2003, several samplings surveys have been conducted in Guadeloupe to evaluate the level of contamination by chlordecone of some species of fish, crustaceans and mollusks, principally species with a high economical interest in order to regulate the fishing activities around the island [ 13 – 18 ]. In 2008, the European Commission of Food Safety set the maximal residue limit (MRL) to 20 μg.kg -1 wet weight for the consumption and commercialization of sea products.…”
Section: Introductionmentioning
confidence: 99%
“…Chlordecone was found into aquatic coastal fauna (Dromard et al 2018) and until pelagic cetacean (Méndez-Fernandez et al 2018). Such results suggest subsequent amount of CLD transferred into the sea and raises the question of the sources, questioning the past or the present provenance of such contamination.…”
Section: Introductionmentioning
confidence: 95%
“…Fish and crustacean are generally more contaminated when they are located downstream the contaminated watersheds and when they are close to the coast (Dromard et al 2017). At the same time, detrivorous and carnivorous organisms generally display higher levels of chlordecone contamination than other trophic groups (Luellen et al 2006;Dromard et al 2017). Our third hypothesis is that chlordecone concentrates in marine organisms, depending on their location (close or far from the source of pollution) and on their feeding ecology.…”
Section: Introductionmentioning
confidence: 89%
“…In Guadeloupe and Martinique, the degree of contamination of marine organisms depends mostly on their location around the two islands (Dromard et al 2016). Fish and crustacean are generally more contaminated when they are located downstream the contaminated watersheds and when they are close to the coast (Dromard et al 2017). At the same time, detrivorous and carnivorous organisms generally display higher levels of chlordecone contamination than other trophic groups (Luellen et al 2006;Dromard et al 2017).…”
Section: Introductionmentioning
confidence: 99%